Increasing the awareness of palm oil plantation replanting through farmers training - Almasdi Syahza; Djaimi Bakce; Brilliant Asmit (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2018)
Palm oil plantation in the Province of Riau has reached the unproductive age and need replanting. Private and government-owned plantation has started the replanting, but plantation community owned. The slow replanting process in smallholders’ palm oil plantation caused by poor knowledge of replanting. This community service objective was to increase the awareness of replanting of palm oil plantation run by smallholders, so it can accelerate the replanting process. We used interactive training method to deliver knowledge related to palm oil plantation replanting. The activity combined indoor and field class to give a better understanding of replanting. The community service activity involved academicians, palm oil practitioners, government institution, and palm oil farmers association. The success of this activity measured by the participant's assessment results through the written test. This training successfully delivered the needed knowledge and experience about palm oil plantation replanting. The knowledge and awareness were expected to accelerate the successful replanting process of palm oil plantation in the Province of Riau.